Pengembangan Media Pembelajaran Video Interaktif sebagai Inovasi Teknologi Pembelajaran untuk Materi Sistem Komputer di SMK pada Era Digital - Arti Fauziah; Irdam Denni; Siti Husnul Bariah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to develop learning media in the form of interactive videos on Computer System material at SMKN 3 Garut, with the expectation of improving learning quality in the digital era. The development process employed the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The learning media was designed by integrating text, animations, images, narration, and interactive features such as digital quizzes to enhance student engagement. The research subjects consisted of 33 tenth-grade students majoring in Computer and Network Engineering. The media was implemented through a learning seminar, where students were given the opportunity to study the material using the developed interactive video. The results showed that the media successfully attracted students’ attention, increased learning motivation, and facilitated understanding of computer system concepts. Teachers also expressed positive responses, as the media helped address limitations in laboratory practice facilities. Based on these findings, the interactive video is considered feasible to be used as an alternative learning resource for Computer System subjects in vocational schools. Further research is recommended to quantitatively examine the effectiveness of the media and to add more interactive features to support independent learning.